PENENTUAN JUMLAH TENAGA KERJA OPTIMAL MELALUI PENGUKURAN WAKTU BAKU DENGAN MENGGUNAKAN METODE STOPWATCH TIME STUDY PADA PEMBUATAN BATU BATA PRESS (STUDI KASUS UD. TIGA SETANGKAI KABUPATEN NAGAN RAYA) - Fitriadi, Fitriadi; Putra, Gaustama; Abdullah, Ali (Universitas Teuku Umar, 2018)
This study aims to determine the optimal number of workers in accordance with the needs of the company and determine the standard time needed for the brick making process. The method used in this study is the stopwatch time study method in which this method is applied to work that lasts briefly and repeatedly (repetitive. Based on the results of the study shows that the optimal amount of labor that should be employed in accordance with the needs of companies in making stone brick press at each work station that is 2 workers with details of workers at the clay excavation station labor that should be employed that is amounting to 2 people, the station put clay into the press machine labor that should be employed that is amounting to 2 people, printing station power the work that should be employed is numbered 2 people, the work station compiles the printout into the wheelbarrow the manpower that should be employed is amounting to 2 people, and the work station compiles the press bricks to the place where the workforce should be employed which is the sum 2 people where the actual number of workers is only 3 people where of the three workers concurrently doing work activities, with the addition of the workforce at each station 1 workforce is expected to achieve production targets and can meet product demand every month at UD. Three Sets of Nagan Raya Regency. The standard time needed for the clay excavation station is 54.78 minutes, the standard time required for the station to enter clay into the press is 41.43 minutes, the standard time required for the brick press molding station is 43.03 minutes, the standard time needed at the work station to compile the printed material into the wheelbarrow is 55.86 minutes, while the standard time required at the work station to compile the brick press to the drying area is 50.17 minutes.